Transformative Learning as a Theoretical Field - Hoggan, Chad; Hoggan-Kloubert, Tetyana (Adult Education Critical Issues, 2024)
The phenomenon of change, of transformation, is just as relevant today as it was in the seventies when the concept of transformative learning was first developed. One might even argue that transformation has gained even more significance globally. This journal issue is a timely inquiry into the current state of its theoretical development, and we are grateful for the opportunity to respond to the questions posed by the editors.